The Development of Mental Health Policies in the Czech Republic and Slovak Republic since 1989 - Dobiášová Karolína (Central European Journal of Public Policy, 2016)
The article aims to describe the key events in the development of mental health care policies after 1990 in the two countries and identify the main reasons for stagnation or incremental changes to the institutional setting in the field of mental health care. The process of mental health care reform is explained using the framework of historical institutionalism. The explanation shows that the lack of political interest in combination with the tradition of institutional care resulted in poor availability of psychiatric care, outdated network of inpatient facilities and critical lack of community care facilities in both countries. Even though Slovak Republic adopted national programme at the governmental level, it still struggles with its implementation. The ongoing reform attempt in the Czech Republic may bring some change, thanks to a new approach towards strategic governance of the mental health care system and the mechanism of layering that the promoters of the reform use.